High-rate fermentative hydrogen production from palm oil mill effluent in an up-flow anaerobic sludge blanket-fixed film reactor - Mohammadi, P.; Ibrahim, S.; Annuar, M.S.M. (Institution of Chemical Engineers, 2014)
The major problem associated with UASB reactors for biotransformation of organic matter to hydrogen is the long start-up period (2–4 months) required for the growth of the microbial granules. In this study, an integration of granular sludge system and a fixed film reactor in a single reactor was applied to overcome this problem. An up-flow anaerobic sludge blanket-fixed film (UASB-FF) reactor was initially inoculated with heat pretreated seed sludge as inoculum and operated as closed-loop fed-batch for five days (HRT = 24 h; 38 °C; pH 5.5). The reactor was continuously fed with fresh pre-settled POME in order to shorten the start-up period. The organic loading was gradually increased from 4.7 to 51.8 g/L d. Granular sludge rapidly developed within 22 days. Specific hydrogen production rate was 0.514 L H2/g VSS d at the end of the start-up period. Speedy development of bio-granules was attributed to biomass recirculation and the establishment of a fixed film at the upper section of the UASB-FF reactor that resulted in improved interactions among the bacterial consortium.